Gender differences in the factors influencing the choice of future career among the final stage Turkish medical students - Ali Jadoo, Saad Ahmed; Dastan, Ilker; Jawdat, Ammar Adnan (Journal of Ideas in Health, 2020)
Background: Turkey has a marked increase in the proportion of female medical students and graduates doctors compared to males. However, females are still underrepresented in some disciplines and grouped in other branches of medicine. It is essential to regularly assess the medical students' trends toward the specialty and avoid the shortage and maldistribution in some critical specialties. This study aims to investigate the gender differences in Turkish medical students’ specialty preferences and influencing factors. Methods: A descriptive cross-sectional study carried out among final year students at the Bezmialem Vakif University (BVU), Faculty of Medicine in Istanbul, Turkey. Data collected from March to April 2018 using a pre-tested self-administered questionnaire included socio-demographic characteristics of the population, first choices for specialization, and the factors influencing those choices. An independent sample t-test performed to test the gender differences in different influencing factors. Data were analyzed using SPSS version 16. Results: A total of seventy (70) students (response rate of 69.5 %) included in the data analysis. The mean age of total respondents was 24.9 ± 0.96 (ranged 23-27), and the male to female ratio of students was approximately 1:1.4. Out of nineteen (19) factors, statistically significant gender differences noted in the mean scores of six factors. Male students were more influenced by family expectations (2.76 ± 0.87, p=0.008), geographical consideration (2.97 ± 0.91, p=0.053), and high income expectations (2.90 ± 0.90, p=0.024) compared to female students. However, female students were more influenced by personal interests (3.61 ± 0.49, p=0.041), personality characteristics (3.59 ± 0.55, p=0.010) and malpractice (2.73 ± 1.03, p=0.015) compared to male students. Conclusion: There is a significant difference between the sexes in terms of priorities; family, income, and geographical distribution significantly impacted on men, while women were more concerned with lifestyle, well-being and avoiding responsibility.